Larval development of the barnacle Amphibalanus improvisus responds variably but robustly to near-future ocean acidification - Pansch, Christian; Schlegel, Peter; Havenhand, Jonathan (ICES Journal of Marine Science, 2013)
Increasing atmospheric CO₂ decreases seawater pH in a phenomenon known as ocean acidification. In two separate experiments we found that larval development of the barnacle Amphibalanus (Balanus) improvisus was not significantly affected by the level of reduced pH that has been projected for the next 150 years. After 3 and 6 days of incubation, we found no consistent effects of reduced pH on developmental speed or larval size at pH 7.8 compared with the control pH of 8.1. After 10 days of incubation, there were no net changes in survival or overall development of larvae raised at pH 7.8 or 7.6 compared with the control pH of 8.0. In all cases, however, there was significant variation in responses between replicate batches (parental genotypes) of larvae, with some batches responding positively to reduced pH. Our results suggest that the non-calcifying larval stages of A. improvisus are generally tolerant to near-future levels of ocean acidification. This result is in line with findings for other barnacle species and suggests that barnacles do not show the greater sensitivity to ocean acidification in early life history reported for other invertebrate species. Substantial genetic variability in response to low pH may confer adaptive benefits under future ocean acidification.